The effect of the fluctuation of the dinar exchange rate against the euro on exports outside of hydrocarbons -An Econometric Study For the case of Algeria 2000-2020- - Mebarek Elkout; Lakhdar Rainouba; Ataellah Chaoui (Dirassat Journal Economic Issue, 2023)
This dissertation aims at studying the impact of exchange rate fluctuations on Algerian non-hydrocarbon exports in international markets for the period 2000 to 2020. Statistical and econometric tools were used (VAR). The study concluded that there was no statistically significant effect of the exchange rate of the Algerian Dinar against the Euro on the exports of non-hydrocarbons. The development of Algerian exports outside hydrocarbons is also largely linked to the development of hydrocarbon exports. This is for the reason that semi-manufactured products, which account for the majority of non-hydrocarbon exports, are mainly hydrocarbon derivatives; consequently, their prices are highly related to hydrocarbon prices. The decline and the collapse of the Algerian Dinar against the Euro due to the depreciation by the monetary authority, which justifies this measure in order to support and encourage Algerian exports. However, this measure is inadequate due to the lack of national production structure and its inability to cover the requirements of the national market in quantity and quality, as well as to be able to access foreign markets. This measure is also attributed to another goal: restricting foreign importations, but then again this reasoning is also considered useless as regards to the needs of the national market and its link with the European market in particular.